Optimisation of the process variables in production of activated carbon by microwave heating. Issue 45 (20th May 2015) - Kundu, Anirban; Gupta, Bhaskar Sen; Hashim, M. A.; Sahu, J. N.; Mujawar, Mubarak; Redzwan, Ghufran
<x xml:space="preserve">Abstract</x> Optimization of process variables in activated carbon preparation by microwave heating for reduction of energy use aiding sustainable development.